The Simulation of the Stabilizing Process of Glass Nanoparticle in Optical Tweezer Using Series of Laser Pulses - Quy, Ho Quang; Hai, Hoang Dinh (Communications in Physics, 2012)
In this article the stable region and stabilizing process of dielectric particle in fluid by the optical tweezer using the series of laser pulses are investigated. The influence of the repetition period and number of laser pulses on the radial variance of particle and the ``so-called’’ stable space-time pillar is simulated and discussed.